UNSKILLED LABORERS IN LAHORE: NAVIGATING INFLATION’S SOCIO-ECONOMIC CHALLENGES - Muhammad Aftab; Ayesha Fayyaz (International Journal of Contemporary Issues in Social Sciences, 2023)
This paper examines the complex interplay of social and economic challenges faced by unskilled workers in a society characterized by persistent inflation over the last four to five years. Their socioeconomic hardships are intertwined with rising inflation rates, leading to a complex web of social problems. Using a qualitative research approach, we conducted 15 in-depth interviews with unskilled daily wage workers in the construction materials industry, including construction supervisors (Mistry), laborers (mazdoor), painters, and loaders. These interviews were conducted in Lahore, Pakistan, around Korey station on Walton Road. The findings of the study shed light on the multifaceted reality faced by unskilled daily wage workers who not only face socioeconomic challenges but also face significant health-related challenges. They also face barriers to accessing government-provided benefits, including the Insaf Sehat Card (a health subsidy program) and the Atta (wheat) Free Program, designed for deserving individuals. To effectively address these problems, it is imperative to establish robust and well-monitored mechanisms managed by dedicated government departments focused on the welfare and development of the poor.